Analysis of the Dimsum Production Process in Culinary MSMEs in Medan City, Indonesia - Muhammad Ibrahim Nasution; Nurhaliza Hasanah; Muhammad Alfi Raifan (Young Journal of Social Sciences and Humanities, 2025)
Culinary MSMEs have a significant contribution to regional economic growth, particularly in Medan, a city recognized for its rich culinary diversity. One product that continues to experience increasing market demand is dimsum. This study aims to analyze the dim sum production system within culinary MSMEs in Medan, focusing on production stages, availability and management of raw materials, the utilization of technology, and obstacles faced during production activities. This research employed a descriptive qualitative method with a case study approach conducted on one MSME that consistently produces dim sum. Data collection techniques included observation, interviews with the business owner, and documentation of production activities. The results reveal that production is still performed semi-manually and lacks structured operational standards, leading to inconsistent product quality and unstable production capacity. Key challenges identified include limited capital, fluctuating raw material prices, and insufficient technical skills among workers. Based on these findings, this study recommends implementing Standard Operating Procedures (SOP), adopting appropriate processing technology, and improving inventory management to enhance production efficiency and competitiveness among culinary MSMEs.